2018
DOI: 10.3390/nu10070848
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Lactoferrin Modulates Dendritic Cell Differentiation and Function

Abstract: Lactoferrin is an abundant glycoprotein in bovine milk that has immunomodulatory effects on human cells. Bovine lactoferrin (LF) binds lipopolysaccharides (LPS) with high affinity and is postulated to act via TLR4-dependent and -independent mechanisms. It has been shown that LF modulates differentiation of human monocytes into tolerogenic dendritic cells. However, in a previous study, we showed that LPS also mediates differentiation into tolerogenic dendritic cells (DC). Since LF binds LPS with high affinity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…More recent data indicate a role for Lf in immune homeostasis as well. Studies indicate that DCs differentiated in the presence of Lf showed decreased responsiveness towards TLR ligands [ 88 , 89 ] and reduced cytokine production demonstrating a potential role for Lf in immune homeostasis. These results indicate a potent anti-inflammatory function for Lf by skewing monocyte differentiation into DCs with impaired capacity for activation and for promotion of Th1 responses and may represent a strategy to block excessive DC activation upon TLR-induced inflammation, adding further evidence for a critical role of Lf in directing host immune function.…”
Section: Immunomodulatory Functions Of Lactoferrinmentioning
confidence: 99%
“…More recent data indicate a role for Lf in immune homeostasis as well. Studies indicate that DCs differentiated in the presence of Lf showed decreased responsiveness towards TLR ligands [ 88 , 89 ] and reduced cytokine production demonstrating a potential role for Lf in immune homeostasis. These results indicate a potent anti-inflammatory function for Lf by skewing monocyte differentiation into DCs with impaired capacity for activation and for promotion of Th1 responses and may represent a strategy to block excessive DC activation upon TLR-induced inflammation, adding further evidence for a critical role of Lf in directing host immune function.…”
Section: Immunomodulatory Functions Of Lactoferrinmentioning
confidence: 99%
“…Lactoferrin (LTF), a normal component of milk and colostrum, which hyrdrolyzes RNA molecules, was also more abundant in milk of both yeast and oat supplemented sows. LTF functions to facilitate binding and transporting iron ions and has antibacterial, antiviral, and antiparasitic properties [ 83 , 84 ]. Enteral supplementation of preterm human infants with LTF was shown to reduce the effects of enteritis in neonates [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whey protein (WP) fraction was purified from the raw bovine milk as described before by Perdijk at al. [48] BLG was purified and isolated as described by De Jongh et al [49] using anion exchange chromatography DEAE Sepharose C-6B (GE healthcare, Chicago, IL, USA). Isolated BLG was lyophilized and of purity >94% was measured as described by Deng et al [20] The LPS removal was performed according to the protocol described by Teodorowicz et al [50] and the Recombinant Factor C Endotoxin Detection Assay (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation and Culturing of Monocyte-Derived Dendritic Cells (MoDCs): Peripheral blood mononuclear cells (PBMCs) were isolated by density centrifugation from fresh blood obtained from healthy anonymous donors as described previously. [48] Monocytes were differentiated into dendritic cells by culturing them for 6 days in the presence of 20 ng mL −1 IL-4 (Peptrotech; 200-04) and GM-CSF (Peprotech; 300-03). After 6 days, immature DCs were used for binding and internalization assays.…”
Section: Methodsmentioning
confidence: 99%